2021
DOI: 10.1088/1741-4326/ac0412
|View full text |Cite
|
Sign up to set email alerts
|

The separatrix operational space of ASDEX Upgrade due to interchange-drift-Alfvén turbulence

Abstract: The efficient operation of a tokamak is limited by several constraints, such as the transition to high confinement or the density limits occurring in both confinement regimes. These particular boundaries of operation are derived in terms of a combination of dimensionless parameters describing interchange-drift-Alfvén turbulence without any free adjustable parameter. The derived boundaries describe the operational space at the separatrix of the ASDEX Upgrade tokamak, which is presented in terms of an electron d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(109 citation statements)
references
References 81 publications
8
101
0
Order By: Relevance
“…In figure 4 we show midplane profiles of α for each case. The range of maximum values α = 0.3 − 1.5 is similar to the range observed in experiments, although in realistic geometry the ideal limit can be somewhat higher so that experimental α values may not exceed the ballooning limit 24,25,63 . The fact that we observe midplane values of α that exceed the ideal ballooning limit α = 1 for our geometry will be examined in a separate paper 64 .…”
Section: Results: Midplane Profiles Heat-flux Width and Transportsupporting
confidence: 75%
See 1 more Smart Citation
“…In figure 4 we show midplane profiles of α for each case. The range of maximum values α = 0.3 − 1.5 is similar to the range observed in experiments, although in realistic geometry the ideal limit can be somewhat higher so that experimental α values may not exceed the ballooning limit 24,25,63 . The fact that we observe midplane values of α that exceed the ideal ballooning limit α = 1 for our geometry will be examined in a separate paper 64 .…”
Section: Results: Midplane Profiles Heat-flux Width and Transportsupporting
confidence: 75%
“…The edge/SOL region features steep pressure gradients, especially in the H-mode transport barrier and SOL regions, which can contribute to the importance of electromagnetic effects. Experimental evidence has indicated that the edge plasma state is controlled by electromagnetic drift-interchange dynamics [23][24][25] . In this regime, the parallel electron dynamics is no longer very fast relative to the drift turbulence, so electrons can no longer be treated adiabatically 26 .…”
Section: Introductionmentioning
confidence: 99%
“…The L-H transition (grey line) occurs when the turbulence suppression by the E × B flow shear caused by the background ion pressure gradient, which is consistent with the neoclassical E × B shear, is stronger than the turbulent growth rate. Additionally diamagnetic and β stabilization of turbulence are included [90]. As shown in figure 9, L-H transitions (grey line) only occur at separatrix densities n e,sep 2.5 × 10 19 m −3 .…”
Section: Importance Of the Outer Plasma Edgementioning
confidence: 99%
“…Extension of the sheath-modified interchange-ballooning analysis in helical geometry presented in [27] to include magnetic shear is left to future work, but we do plot α = γ 2 int /(k 2 0 v 2 A ) = (L c /π) 2 (β e + β i )/(RL p ) evaluated at the midplane in figure 6, where here k 0 = π/L c itself varies with radius because of the variation of L c . Taking the peak α value from each the case, we have a range α ≈ 0.3 − 3, which is in the range of mea-surements of α in the near SOL of present experiments [39,40,41].…”
Section: Resultsmentioning
confidence: 67%